2020
DOI: 10.1038/s41421-020-0183-x
|View full text |Cite
|
Sign up to set email alerts
|

A bioenergetic shift is required for spermatogonial differentiation

Abstract: A bioenergetic balance between glycolysis and mitochondrial respiration is particularly important for stem cell fate specification. It however remains to be determined whether undifferentiated spermatogonia switch their preference for bioenergy production during differentiation. In this study, we found that ATP generation in spermatogonia was gradually increased upon retinoic acid (RA)-induced differentiation. To accommodate this elevated energy demand, RA signaling concomitantly switched ATP production in spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 65 publications
2
30
0
Order By: Relevance
“…Upregulation of genes associated with glycolysis and hypoxia was detected in early differentiating spermatogonia of UCH-1 −/− , as opposed to the physiological switch towards OXPHOS in the wild-type. Hence, UCH-L1 deficiency altered the bioenergetic equilibrium between glycolysis and OXPHOS that is necessary for spermatogonial proliferation and differentiation [58]. These data suggest that UCH-L1 is required for maintenance of proper mitochondrial activity and its upregulation leads to impaired function of SSCs, impairing SSC metabolic and differentiation competence.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Upregulation of genes associated with glycolysis and hypoxia was detected in early differentiating spermatogonia of UCH-1 −/− , as opposed to the physiological switch towards OXPHOS in the wild-type. Hence, UCH-L1 deficiency altered the bioenergetic equilibrium between glycolysis and OXPHOS that is necessary for spermatogonial proliferation and differentiation [58]. These data suggest that UCH-L1 is required for maintenance of proper mitochondrial activity and its upregulation leads to impaired function of SSCs, impairing SSC metabolic and differentiation competence.…”
Section: Discussionmentioning
confidence: 87%
“…It is becoming increasingly evident that maintaining metabolic integrity and plasticity is pivotal for SSC function [33,49,57]. Anaerobic metabolism is necessary for SSC maintenance in vivo and in vitro [33,49], while SSCs upregulate mitochondrial activity with differentiation [40,42,49,58]. The protection of this metabolic balance by preserving the metabolic integrity of SSCs is essential to maintaining the differentiation potential of SSCs, which gradually diminishes in aging cells [58].…”
Section: Discussionmentioning
confidence: 99%
“…7E, I ). AP-III-a4 is a non-substrate analog that directly binds to enolase and inhibits its function independent of enzymatic activity, which has been widely used in elucidating the role of ENO1 in many kinds of tumors 24 , 26 , 27 . AP-III-a4 decreased the number of HCT116-FAP and HCT8-FAP cells, and inactivated NF-κB signaling pathway (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This is a bioenergenic balance between glycolysis and oxidative phosphorylation, which can be disrupted in the absence of oxygen. Recent research has found that the inhibition of mitochondrial respiration and glycolysis in undifferentiated spermatogonia cells results in decreased spermatogonial colony size, and reduced expression of SSC marker genes, such as Plzf, Id4, Gfrα1, Etv5, and Sall4, suggesting that hypoxia may affect spermatogonia differentiation ( Chen et al, 2020 ).…”
Section: Reproductive Consequences Of Hypoxiamentioning
confidence: 99%